Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan pada Apotek Rafa Farma Surabaya - Jelita Amalia Putri; Iswati Iswati; Siti Aisah; Anis Fitriyasari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research is aimed at understanding in more detail "quality of service and price on customer satisfaction" in accordance with the problem raised, which is the effect of service quality and price on customer satisfaction at Drug Store Rafa Farma Surabaya. The researcher assumes that service quality and price have a positive and significant effect on customer satisfaction. This research uses primary data obtained from direct observation and questionnaires distributed to respondents, which will then be analyzed using multiple linear regression.